Bounded – The neglected threshold concept characteristic. Issue 3 (3rd May 2020) - Barradell, Sarah; Fortune, Tracy
ABSTRACT: The threshold concepts framework provides educators with a useful way of thinking about the struggles students have in coming to know essential, hard to grasp knowledge. A threshold concept is often best understood through reference to eight characteristics that together describe what is critical to effective knowledge acquisition. This conceptual paper hones in on just one of these characteristics – the bounded quality – that we propose is the most overlooked, but important, of the characteristics. The bounded characteristic frames the unique knowledge of a discipline and reflects its particular world-view. In this critical review, we analyse examples from threshold concepts scholarship: first, to explore the limitations of overlooking what the bounded characteristic has to offer, and second, to show how attention to ways of thinking and practising (WTP), may help to bring the bounded characteristic into focus, and reveal it as another non-negotiable threshold concept characteristic.